Has Interprofessional Education Changed Learning Preferences? A National Perspective. (18th March 2016) - Kashner, T. Michael; Hettler, Debbie L.; Zeiss, Robert A.; Aron, David C.; Bernett, David S.; Brannen, Judy L.; Byrne, John M.; Cannon, Grant W.; Chang, Barbara K.; Dougherty, Mary B.; Gilman, Stuart C.; Holland, Gloria J.; et al.
Abstract : Objective: To assess how changes in curriculum, accreditation standards, and certification and licensure competencies impacted how medical students and physician residents value interprofessional team and patient‐centered care. Primary Data Source: The Department of Veterans Affairs Learners' Perceptions Survey (2003–2013). The nationally administered survey asked a representative sample of 56, 569 U.S. medical students and physician residents, with a comparison group of 78, 038 nonphysician trainees, to rate satisfaction with 28 elements, in two overall domains, describing their clinical learning experiences at VA medical centers. Study Design: Value preferences were scored as independent adjusted associations between an element (interprofessional team, patient‐centered preceptor) and the respective overall domain (clinical learning environment, faculty, and preceptors) relative to a referent element (quality of clinical care, quality of preceptor). Principal Findings: Physician trainees valued interprofessional (14 percent vs. 37 percent, p  < .001) and patient‐centered learning (21 percent vs. 36 percent, p  < .001) less than their nonphysician counterparts. Physician preferences for interprofessional learning showed modest increases over time (2.5 percent/year, p  < .001), driven mostly by internal medicine and surgery residents. Preferences did not increase with trainees' academic progress. Conclusions: Despite changes in medical education, physician trainees continue to lag behind their nonphysician counterparts in valuing experience with interprofessional team and patient‐centered care.